Fitoremediation for the Rehabilitation of Agricultural Land Contaminated by Cadmium and Copper - N. SUTRISNO SA'AD; R ARTANTI; T DEWI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
There are many agricultural land using irrigation water from polluted industrial waste of heavy metals. Improvement of agricultural land quality using fitoremediation is needed to overcome heavy metal pollution. The reasearch aims to make remedies for paddy field polluted by cadmium (Cd) and copper (Cu) using plants that have the ability to absorb heavy metals in order to increase the quality of the land. This research was conducted at the screen house of Indonesian Agricultural Enviroment Research Institute, using a Randomize Block Design (RBD). Hyperaccumulator treatment plant, consisting of T1: mendong (Fimbristylis globulosa), T2: grass types tekian (Cyperus platystylis), T3: jugul (Borreria laevis), T4: spinach (Amaranthus spp.), T5: mustard (Brassica juncea), T6: bundung ganal (Scleria poaeformis), T7: purun tikus (Eleocharis dulcis), T8: karapiting (Polygonum hydropiper), T9: hiring-hiring (Rhynchosphora corynbosa), and T10: purun kudung (Leperonia mucrunata). The results showed that the content of heavy metals Cd and Cu in Vertisols (Sambung Macan and Sragen) are 1.18 and 31.38 ppmrespectively. All hyperaccumulator plants on Vertisols polluted by cadmium (Cd) can reduce the levels of soil cadmium after two months planted (Duncan test level 5%). The content of copper (Cu) in soil indicated an increase and significantly different (Duncan test level 5%). Purun kudung is significantly different compared with mustard in term of Cu adsorption from soil. The Cu content on two months old spinach is higher than othertreatments, but the highest Cu content occurs on stems and leaves of jugul plant. The content of cadmium (Cd) on roots of jugul plant is the highest and significantly different, while thecontent of Cd on hiring-hiring plant is also the highest content but not significantly different.